Children's Approximate Number System in Haptic Modality. (January 2016) - Gimbert, Fanny; Gentaz, Edouard; Camos, Valérie; Mazens, Karine
The approximate number system (ANS) is a primitive system used to estimate quantities. It can process quantities in visual and auditory modalities. The aim of the present study was to examine whether ANS can process quantities presented haptically. Moreover, to assess age-related changes, two groups of children (5- and 7-year-olds) were compared. In a newly designed haptic task, children compared two arrays of dots by touching them simultaneously using both hands, without seeing them, and for limited duration to prevent counting. Using Panamath, a frequently used visual ANS task, we verified that our population exhibited the typical pattern of approximation with visual arrays: Older children outperformed younger children, and an increased ratio between the two quantities to be compared led to more accurate responses. Performance in the haptic task revealed that children, in both age-groups, were able to haptically compare two quantities above chance level, with improved performance in older compared with younger children. Moreover, our results revealed a ratio effect, a well-known signature of the ANS. These findings suggest that haptic numerical discrimination in children is dictated by the ANS, and that ANS acuity measured with a haptic task improves with age, as commonly observed with the visual task.